Recent trends and perspectives of carbon-based nanocomposites for multifunctional applications - Irandoost, Maryam; Heidari, Fatemeh (Journal of Composites and Compounds, 2024)
Carbon-based nanocomposites are a new type of multifunctional materials that combine mechanical, electrical, and thermal properties in a unique and useful manner and have allowed the use of these materials to change technology. The latest trends indicate that there are many significant advancements occurring in the development of carbon nanotube-enhanced polymer nanocomposite materials. Carbon-based nano composites offer superior performance compared to other types of conventional materials. There is an ongoing direction toward developing innovative design and manufacturing techniques for carbon-based nanocomposites, through sustained investment into new product development, research, and development of next generation multi-functional carbon-based nanocomposite products for cutting-edge application technologies.